2021
DOI: 10.1108/jsm-11-2020-0472
|View full text |Cite
|
Sign up to set email alerts
|

Consumer responses to environmental corporate social responsibility and luxury

Abstract: Purpose Drawing on the stimulus–organism–response (S-O-R) framework, this study presents an original model examining the influence of environmental corporate social responsibility (CSR), luxury and service quality dimensions on consumer emotions that in turn influence consumer attitudes towards the shopping mall. Design/methodology/approach Structural equation modeling is applied to data from a sample of 706 French consumers to test the hypotheses. Findings The results highlight the importance of environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…While stimuli are the signals sent by the firm and are external to the individual customers, they could affect how customers feel about the firm and ultimately alter their response. Schill and Godefroit-Winkel (2022) argued that environmental CSR can play a role ( stimuli component ) to represent the characteristics of the firm and result in enhanced customer experience. It is assumed that an established level of CEDs ( organism component ) in turn would influence critical customer outcomes ( response component ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…While stimuli are the signals sent by the firm and are external to the individual customers, they could affect how customers feel about the firm and ultimately alter their response. Schill and Godefroit-Winkel (2022) argued that environmental CSR can play a role ( stimuli component ) to represent the characteristics of the firm and result in enhanced customer experience. It is assumed that an established level of CEDs ( organism component ) in turn would influence critical customer outcomes ( response component ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…However, previous research remains scarce in exploring the impact of environmental CSR as an important concern that could potentially influence customer equity and lead to critical behavioral outcomes in the airline industry. Considering the negative environmental impacts of the airline industry (Kim, Lee & Roh, 2020) and an urge to pursue environmental CSR in the service industry (Schill & Godefroit-Winkel, 2022), such a void in tourism sustainability literature sounds significant.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al (2020) examined the effects of CSR on CA toward a sport sponsorship and found positive influence. Further, Schill and Godefroit-Winkel (2021) examined the influence of CSR on consumer emotions which in turn influence CA towards the shopping mall. Most recently, Ng (2022) investigated how perceived CSR relate to CA regarding social enterprise products and found positive effects.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Despite the importance of social responsibility in reducing harmful effects on the environment through integration and interactions between all stakeholders, whether suppliers or consumers [9], studies that dealt with the relationship between ECSR and consumer behavior or marketing variables are very limited [8]. The notion that environmental responsibility is an essential component of CSR seems less contentious than the diverse nature of CSR discussed before.…”
Section: Introductionmentioning
confidence: 99%